SPECTRUM OF ISLAMIC EDUCATION MANAGEMENT - Muslim; Garianto (IAI AGUS SALIM METRO LAMPUNG, 2022)
Management of Islamic education, its characteristics and spectrum. The characteristics of Islamic education management must be based on the Qur'an and Hadith as well as rational thinking that has been tested for validity. The spectrum of Islamic education management includes the scope of Islamic education personnel management, Islamic student education management, Islamic education curriculum management, Islamic education financial management, Islamic education facilities and infrastructure management, public relationsmanagement, Islamic community education services, Islamic education quality management, management Islamic education change, Islamic education structure management, Islamic education conflict management, Islamic education and communication management.